The effect of a training program to develop the speed of motor response to the skill of the forehand in the game of tennis (Journal of the College of Basic Education, 2022)
The research included five chapters:The first chapter included the introduction and the importance of the research, as the game of tennis occupies a distinguished place in the world, like the rest of the other sports, and the interest in it is increasing, and it has become aroused by the interest of many in many countries of the world because of its characteristics and requirements that are characterized by excitement and suspense and the increase in demand for its practice is a summary Serious scientific planning in all game requirements in terms of developing its missions